ANALYSIS OF FOOD SECURITY AND SURVIVAL STRATEGIES OF FISHERMEN'S HOUSEHOLDS IN PURWOREJO DISTRICT - Savitri, Nurul; Marwanti, Sri; Nadifta Ulfa, Amalia (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Food security is a condition where a person can access sufficient, safe and nutritious food to meet daily nutritional needs. Not everyone can meet their food needs, especially poor households such as fishing households. This makes survival strategies important for everyone. The purpose of this study was to determine the amount of food expenditure towards the total expenditure of fishermen's households, calculate the amount of energy consumption of fishermen's households, analyze the food security conditions of fishermen's households, and determine the survival strategies of fishermen's households. The basic method of this research is descriptive method. The research location is in Purworejo Regency. The sample determination method is purposive sampling. The types of data used are primary and secondary data. Data collection methods are observation, interviews, recall, and recording. Data analysis methods are (1) Analysis of the Proportion of Food Consumption to Total Household Expenditures; (2) Analysis of Energy Consumption Levels; (3) Food Security Analysis; (4) Survival Strategy Analysis. The results of this research are that the proportion of food expenditure by fishermen households in Purworejo Regency is quite good, namely 55% A good level of food expenditure proportion is less than 60%. Fisherman household energy consumption in Purworejo Regency is in the medium category, namely 88,95%. The food security conditions of fishing households in Purworejo Regency are 56,82% food security, 40,91% food vulnerability, 2,27% food shortage, 0% food insecurity. The survival strategies applied are an active strategy by having a side job, and a networking strategy by asking for help from other parties. Keywords: Fishermen’s households, food security, survival strategies